Transportation security - Bragdon, Clifford R. (BH/Elsevier, 2008)
Insecure transportation systems are costing our worldwide mobility-based economy as much as 6% of GDP annually. The effectiveness of security measures vary widely. In the United States, depending on the mode of transportation, it ranges from "medium effectiveness" for airports to "low effectiveness" for maritime, rail, transit, and intermodal activities. Situational awareness and interoperability are lacking as we try to deal with both natural and man-made disasters. Regardless of the transport mode, improvements are essential if governments and corporations are to address security planning, r.
Keywords: Transportation -- Security measures.; elektronické knihy; electronic books